INVESTIGATION OF THE PHYSICAL PROPERTIES OF MnNi₍₁₋ₓ₎Mₓ ALLOYS WHERE M=Ti, Al - HIRIAN, Răzvan; MERCEA, A.; POP, Viorel (Studia Universitatis Babeș-Bolyai Physica, 2022)
Mn50Ni50-xMx, where M= Ti, Al and x=0, 2.5, 5 and 10, alloys with the L10 crystal structure were successfully synthesized. The martensite type transformation was fond to be strongly affected by doping. Both x=10 samples show a spin glass type behavior while the sample doped with Al also shows large exchange bias.